Business Ethics and Economic Viability in the Niger Delta Region, South-South, Nigeria - Kingsley N, Anyanwu (American Journal of Economics and Business Management, 2023)
This study examines business ethics and economic viability in the Niger Delta Region. Two research objectives, questions as well as hypotheses were proposed to guide the study. Data was generated from primary data, the questionnaire was the major instrument used to generate data. The researcher used simple percentage and ANOVA to analyze the data collected. Simple percentage was used to determine the respondents’ percentage responses in any of the questions, while analysis of variance (ANOVA) was used to test the hypothesis. The findings show that there is significant relationship between ethical principles and infrastructural development in Niger delta region. Also the findings from the second hypotheses testing indicated that there is a significant relationship between ethical value and employment generation. The study recommends that organizations should be ethically responsible on infrastructural development within their region of operation as this will enhance economic viability also that organizations should be ethically and socially responsible and ensure that their operation concentrate on human capital development.